QI Project to Reduce Non-Leftover Medication Wastage in Haramaya University Hiwot Fana Chomprensive Specialized Hospital Pediatrics Ward, Harar, Ethiopia - Tadesse, Tilahun; Amin, Abdi; Hagose, Bisrat; Abebe , Eyoel; Teshome, Melaku; Hailu, Samson; Getu, Muluken; Mulugeta, Aduga; Molla, Yohannes; Ahmed, Abdulbasit (International Journal of Economic, Finance and Business Statistics, 2023)
Non-leftover medication wastage refers to medications dispensed out but not used by patients as they are not in the treatment regimen. This project aims to reduce non-leftover medication wastage in Haramaya University - Hiwot Fana Comprehensive Specialized Hospital (HrU-HFCSH) pediatric ward, Harar, Ethiopia.Baseline assessment showed that, 23 % Of medications dispensed from single dispensary were not administered to the patient as they were not in the treatment regimen. This implies that, 29 % of cost of medications dispensed from a single dispensary were wasted.Before-and-after study was conducted. All data were converted into monitory value and presented as % wastage and % discrepancy. Medications which are dispensed but not used by the patient were considered as wasted if they were not in the treatment regimen.Monitoring of discrepancy in medication supply and administration data.Overall there were 24.65 % reduction in % wastage (financial), 18.65 % reduction in % wastage (product) and 15 % reduction in % discrepancy from the baseline.The findings of this project indicate the importance of monitoring discrepancies in medication supply and administration data in reducing non-leftover medication wastage.